DAMPAK KEBIJAKAN FISKAL DAN MONETER PASCA PANDEMI COVID 19 TERHADAP HARGA SAHAM DI INDONESIA - Nadya Ananda Effendi; Silvia Anggrie Nst; Muhammad Aldrian Oktofa; Muhammad Ikhsan Harahap (EKSYA : Jurnal Ekonomi Syariah, 2023)
The development of the stock market is currently very developed along with the advancement of technology today. It can be seen that many people have used technology such as the internet. Making the stock market buzz even bigger. And also led to the emergence of many companies / new entrepreneurs. And also with the many companies and new entrepreneurs, they have to join the stock market. Because the participation of these companies makes them benefit by obtaining additional funds for their companies so that their companies can expand their companies so that they are known to the public. corners of the world. However, this was hampered due to the Covid-19 pandemic in early 2020 until the June 2022 period. During that time the stock market in Indonesia was very, very damaged, because of the pandemic. There were many restrictions on economic transactions that caused the economy to collapse. Many companies have experienced losses and even bankruptcy because of the effects of this pandemic. Because of this, the government also took economic policies, namely, by implementing fiscal and monetary policies, which are expected to make good reforms for the Indonesian economy